2018
DOI: 10.1111/echo.13876
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial structure and function in patients with hypertension and with chronic heart failure

Abstract: In an outpatient HF cohort, both lower RAEF and increased RAVI were associated with other markers of impaired cardiac function and 12-month adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…RA volume has been identified as an independent predictor of the adverse events in the patients with HF assessed on both the MRI and echocardiography (7,8). Larger RAVI and lower RAEF were associated with the 12-month HF hospitalizations or death irrespective of age, sex, and prior AF (11). This study shows the relation of BMI with the RA function measured by echocardiography that did not show a significant correlation.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…RA volume has been identified as an independent predictor of the adverse events in the patients with HF assessed on both the MRI and echocardiography (7,8). Larger RAVI and lower RAEF were associated with the 12-month HF hospitalizations or death irrespective of age, sex, and prior AF (11). This study shows the relation of BMI with the RA function measured by echocardiography that did not show a significant correlation.…”
Section: Discussionmentioning
confidence: 64%
“…An inverse association between the increased RA volume index (RAVI) and impaired RA emptying fraction (RAEF) has been reported in the patients with pulmonary arterial hypertension assessed by either echocardiography or MRI (9,10). Both the larger RAVI and lower RAEF were associated with the 12month HF hospitalizations or death irrespective of age, sex, and prior AF (11). It is unclear whether the alterations in atrial function observed in adipose patients are solely explained by the systemic effects (mechanical load, inflammation).…”
Section: Introductionmentioning
confidence: 99%
“…Systemic hypertension also impacts the right ventricle (RV), resulting in concentric RV remodeling and impaired RV diastolic function [ 137 , 138 ]. Numerous clinical studies have linked adverse RV remodeling to an unfavorable prognosis [ 139 , 140 , 141 ]. Right heart involvement may be attributed to pulmonary hypertension secondary to left heart conditions [ 142 ].…”
Section: Mechanisms Contributing To Hypertensive Heart Diseasementioning
confidence: 99%
“…A maximális JP-i volumen, illetve testfelszínre indexált ben írták le. HFrEF-betegekben a JPVI összefüggést mutatott a betegek funkcionális állapotával, valamint a mortalitás és egyéb adverz események független prediktorának bizonyult (26)(27)(28)(29)(30). Hasonló eredmények születtek PAH-populációban is (31,32).…”
Section: A Jobb Pitvar Méretének Klinikai Jelentőségeunclassified